PURCHASE INTENTION PADA GEOTAGGING TIKTOK: PERAN PERFORMANCE EXPECTANCY, SOCIAL INFLUENCE, DAN PRICE VALUE - Usmani, Nadhia Mananda; Vania, Amelindha (JURNAL LENTERA BISNIS, 2026)
The rapid development of social commerce platforms has transformed consumer purchasing behavior, particularly through location-based promotional features. Despite growing scholarly interest in purchase intention on digital platforms, empirical findings regarding the roles of performance expectancy, social influence, and price value remain inconsistent, and studies specifically addressing location-tagged food voucher promotions on TikTok are still limited. This study aims to examine the influence of performance expectancy, social influence, and price value on purchase intention among TikTok users exposed to food voucher promotions through the geotagging feature in Malang City. A quantitative approach was employed through a survey method involving 130 respondents selected via purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results demonstrate that all three variables positively and significantly influence purchase intention, both partially and simultaneously. Performance expectancy yielded a path coefficient of 0.264 (T-statistic = 2.647; p = 0.008), social influence of 0.276 (T-statistic = 3.631; p = 0.000), and price value emerged as the most dominant predictor with a path coefficient of 0.348 (T-statistic = 3.018; p = 0.003). Collectively, the three variables explain 63.1% of the variance in purchase intention (R² = 0.631). These findings confirm that consumers' perceived benefit of the feature, social recommendations within the platform, and the perceived economic value of vouchers are the primary drivers of purchasing intent in TikTok's geotagging ecosystem. Food and beverage SME practitioners are encouraged to optimize TikTok's geotagging feature by emphasizing functional benefits, leveraging user-generated recommendations, and offering competitively priced vouchers to effectively stimulate consumer purchase intention.